Tropical wood polymer nanocomposite (WPNC): The impact of nanoclay on dynamic mechanical thermal properties - Md. Saiful, Islam; Sinin, Hamdan; Zainal Abidin, Talib; Abu Saleh, Ahmed; Md. Rezaur, Rahman (Elsevier, 2012)
In this study, wood polymer nanocomposites (WPNCS) were manufactured from five Malaysian tropical wood species by vacuum-impregnation attended by in situ polymerization using phenol–formaldehyde resin and montmorillomite nanoclay. Percentage weight gain and density of wood polymer nanocomposites depended on wood species. Thermo-mechanical properties of wood samples were investigated by the dynamic mechanical thermal analysis (DMTA) over the temperature range of 100 C to 200 C. The intrinsic properties of the components, morphology of the system and the nature of interface between the phases were also determined through DMTA test. Storage modulus (E0) of WPNC samples exhibited significant improvement over the temperature range, in both glassy region and rubbery plateau in relation to their corresponding raw wood samples and wood polymer composites (WPCs). Furthermore, damping (loss tand) peaks of all wood species were lowered by PF-Nanoclay system treatment, an indication of improved surface interphase of wood. Dynamic Young’s modulus (Ed) of wood was also calculated using free–free vibration testing. A significant increment was obtained for the PF-Nanoclay impregnated WPNC samples.